Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11069-015-1855-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple DEM assessment procedure for gully system analysis in the Lake Manyara area, northern Tanzania

Abstract: Gully erosion is a major threat concerning landscape degradation in large areas along the northern Tanzanian Rift valley. It is the dominant erosion process producing large parts of the sediments that are effectively conducted into the river network. The study area is located in the Lake Manyara-Makuyuni River catchment, Arusha, northern Tanzania. During fieldwork, we measured topographic data of eight gully systems close to Makuyuni Town. The main focus of this study is to assess gully erosion dynamics using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In contrast, the reference ASTER DEM with a coarser resolution (30 m) achieved an F1 score of 72.17%. Thus, our study confirmed that it is feasible to extract gullies from lower-resolution DEMs by employing suitable information enhancement methods, as suggested by Maerker et al [71].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the reference ASTER DEM with a coarser resolution (30 m) achieved an F1 score of 72.17%. Thus, our study confirmed that it is feasible to extract gullies from lower-resolution DEMs by employing suitable information enhancement methods, as suggested by Maerker et al [71].…”
Section: Discussionsupporting
confidence: 87%
“…While the amount of grazing land has decreased, the number of livestock in the area has, like the rest of Tanzania, doubled in the same period, seriously increasing livestock densities and grazing pressures (FAO, 2019). The combination of these land-use changes with a natural high vulnerability to soil erosion has resulted in a marked increase in surface erosion, gully incision and land degradation in the area (Blake et al, 2018;Kiunsi & Meadows, 2006;Maerker et al, 2015). The combination of land degradation by erosion and siltation of the water bodies threatens ecosystem health and service provision in the region (Janssens de Bisthoven et al, 2020).…”
Section: Study Sites and Coring Strategymentioning
confidence: 99%
“…Smaller pockets of forest and wetland vegetation are confined to the uplands and floodplains, respectively. However, a combination of unsustainable land-cover changes and a natural high vulnerability to soil erosion resulted in a marked increase in surface erosion, gully incision and land degradation in the area (Blake et al, 2018b;Kiunsi & Meadows, 2006;Maerker et al, 2015;Wynants et al, 2018). Therefore, three sub-catchments (Figure 1 and Table 1) were selected for a detailed investigation into the sources of transported sediment: Nanja, weathered soils, medium to steep slopes and variable rainfall levels.…”
Section: Study Areamentioning
confidence: 99%